Pelaksanaan Otonomi Daerah dalam Konteks Hukum dan Politik Nasional - Djuniarti Djuniarti; Abdul Azis; Harlina Hamid; Hambali Hambali (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
Regional autonomy is an important concept in the system of government in Indonesia, which aims to give freedom and authority to the regions in managing government and development affairs. This study aims to analyze the implementation of regional autonomy from the perspective of national legal politics by focusing on several regions in Indonesia. This research uses a qualitative method with a case study approach. Data were obtained through in-depth interviews with local government officials, legislators, academics and other stakeholders involved in the implementation of regional autonomy. Apart from that, data was also collected through analysis of documents and policies related to regional autonomy. The results of the research show that the implementation of regional autonomy in Indonesia still faces several political and legal challenges. There are tensions between the central and regional governments regarding the division of powers and the allocation of resources. Some regions have succeeded in implementing autonomy properly, while there are also regions that have experienced problems in optimizing the authority they have. Political factors, such as local political dynamics, the influence of political parties and certain political interests, influence the implementation of regional autonomy. In addition, legal aspects, including complex laws and regulations and differences in legal interpretation between the central and regional governments, are also obstacles in the implementation of autonomy. This research produces policy recommendations to improve the implementation of regional autonomy in Indonesia. A more comprehensive approach is needed to improve coordination between the central and regional governments in making strategic decisions. Strengthening capacity and fostering human resources at the regional level is also the key to increasing the implementation of regional autonomy that is more effective and efficient from the perspective of national legal politics.